COVID-19 vaccine acceptance in Notoprajan, Yogyakarta, Indonesia: a lesson learned from the pandemic - Nugraheni, Aulia Putri; Sulistyawati, Sulistyawati (Intelektual Pustaka Media Utama, 2023)
COVID-19 vaccination began in Indonesia in January 2021, with a minimum target coverage of 70% of the population. The government has delivered four doses of the COVID-19 vaccine, but doses three and four have yet to meet the target. Public acceptance of the COVID-19 vaccination has varied due to the speed of the introduction and implementation of this vaccination. Meanwhile, basic information about the factor’s influencing acceptance has yet to be widely known. This study aimed to determine the relationship between sociodemographics and COVID-19 vaccine acceptance in Notoprajan, Yogyakarta, Indonesia. A cross-sectional study was used for this analytic survey. The population is 4,726 people, and the sample size is 355 people. People between the ages of 17 and 55 were eligible, as were those who had lived in Notoprajan, Ngampilan District, Yogyakarta, for at least three months. The data were analyzed using descriptive and bivariate analysis with a 95% confidence level (α=0.05) using the Chi-square statistical test. Among the six observed variables, namely age, gender, education, occupation, religion, and knowledge level, only sex significantly correlates with COVID-19 vaccine acceptance. This research indicates that to increase COVID-19 vaccination, related parties need to target women directly. This is because men received 1.47 times the COVID-19 vaccination from this study compared to women.